Prevalence of placenta praevia by world region: a systematic review and meta‐analysis. Issue 6 (1st April 2013) - Cresswell, Jenny A.; Ronsmans, Carine; Calvert, Clara; Filippi, Véronique
Abstract Objectives (i) To estimate the prevalence burden of placenta praevia in each world region, and (ii) to investigate potential sources of heterogeneity. Methods Systematic review of the literature and random‐effects meta‐analysis. Potential sources of heterogeneity were investigated using meta‐regression. Results The overall prevalence of placenta praevia was 5.2 per 1000 pregnancies (95% CI: 4.5–5.9). However, there was evidence of regional variation (P = 0.0001); prevalence was highest among Asian studies (12.2 per 1000 pregnancies; 95% CI: 9.5–15.2) and lower among studies from Europe (3.6 per 1000 pregnancies; 95% CI: 2.8–4.6), North America (2.9 per 1000 pregnancies; 95% CI: 2.3–3.5) and Sub‐Saharan Africa (2.7 per 1000 pregnancies; 95% CI: 0.3–11.0). The prevalence of major placenta praevia was 4.3 per 1000 pregnancies (95% CI: 3.3–5.4). Conclusion The prevalence of placenta praevia is low at around 5 per 1000 pregnancies. There is some evidence suggestive of regional variation in its prevalence, but it is not possible to determine from existing data whether this is due to true ethnic differences or other unknown factor(s).